(untitled) - Singh, B P (New Delhi, 2005)
The stable isotopes of hydrogen and oxygen of water molecule, environmental radioactive isotopes 3H, 10Be, 14C, 26Al, 32Si, 36Cl, 39Ar, 53Mn, 59Ni, 81Kr and 137Cs, nuclear explosion- produced 3H, 36Cl, 85Kr, 129I are some of the isotopes which have played a vital role in understanding the movement of water in hydrological cycle especially in hydrology, hydrogeology and water resources. There are many other radioactive isotopes specially 131I, 82Br, 22Na 198Au and other short-lived isotopes which are used as tracers. Further gamma radiations from many radioactive isotopes, specially 137Cs, 134Cs, 60Co and neutrons from Radium Beryllium and other sources, all as sealed sources, have been found very useful for understanding movement of water and sediments in the hydrological systems. This requires the basic understanding of the isotopes, their interaction with matter and also their detection in laboratory and in situ conditions.
Keywords: Radioisotopes in hydrology,Stable isotopes,Đồng vị hoá học trong thuỷ học